Brassinosteroids control meristem size by promoting cell cycle progression in Arabidopsis roots - González García, Mary Paz (2011)
Brassinosteroids (BRs) play crucial roles in plant growth and development. Previous studies have shown that BRs promote cell elongation in vegetative organs in several plant species, but their contribution to meristem homeostasis remains unexplored. Our analyses report that both loss- and gain-of-function BR-related mutants in Arabidopsis thaliana have reduced meristem size, indicating that balanced BR signalling is needed for the optimal root growth. In the BR-insensitive bri1-116 mutant, the expression pattern of the cell division markers CYCB1;1, ICK2/KRP2 and KNOLLE revealed that a decreased mitotic activity accounts for the reduced meristem size; accordingly, this defect could be overcome by the overexpression of CYCD3;1. The activity of the quiescent centre (QC) was low in the short roots of bri1-116, as reported by cell type-specific markers and differentiation phenotypes of distal stem cells. Conversely, plants treated with the most active BR, brassinolide, or mutants with enhanced BR signalling, such as bes1-D, show a premature cell cycle exit that results in early differentiation of meristematic cells, which also negatively influence meristem size and overall root growth. In the stem cell niche, BRs promote the QC renewal and differentiation of distal stem cells. Together, our results provide evidence that BRs play a regulatory role in the control of cell-cycle progression and differentiation in the Arabidopsis root meristem.